2019
DOI: 10.1142/s021812661950230x
|View full text |Cite
|
Sign up to set email alerts
|

A Miniaturized High-Gain (MHG) Ultra-Wideband Unidirectional Monopole Antenna for UWB Applications

Abstract: A miniaturized high-gain (MHG) ultra-wideband (UWB) unidirectional monopole antenna with defected ground structure (DGS) is designed for ultra-wideband applications. The MHG antenna is printed on the FR4 substrate material with an overall size of 26.6-mm [Formula: see text] 29.3-mm [Formula: see text] 1.6-mm, which operates over the UWB frequency range and achieves the bandwidth between 3.1[Formula: see text]GHz and 10.6[Formula: see text]GHz. This high-gain unidirectional antenna exhibits a peak gain of 7.20[… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…15 GHz respectively are calculated from the -10 dB line shown in Figure 3. The calculated bandwidth of this antenna is 19.7 GHz (fractional bandwidth of 151.54%), which is better than that observed in refs [10]- [13], covering the X-band, C-band, Ku band, S-band, scanning tunneling microscopy (STM) band applications, and other wireless applications such as worldwide interoperability for microwave access (WiMAX), Wi-Fi, wireless local area network (WLAN), radio astronomy, military communication, communications and sensors, position location and tracking, satellite communication, and radar communication.…”
Section: Resultscontrasting
confidence: 48%
See 1 more Smart Citation
“…15 GHz respectively are calculated from the -10 dB line shown in Figure 3. The calculated bandwidth of this antenna is 19.7 GHz (fractional bandwidth of 151.54%), which is better than that observed in refs [10]- [13], covering the X-band, C-band, Ku band, S-band, scanning tunneling microscopy (STM) band applications, and other wireless applications such as worldwide interoperability for microwave access (WiMAX), Wi-Fi, wireless local area network (WLAN), radio astronomy, military communication, communications and sensors, position location and tracking, satellite communication, and radar communication.…”
Section: Resultscontrasting
confidence: 48%
“…The simulation result of the variation in antenna gain as a function of frequency is shown in Figure 7. It is apparent that the gain increases with increasing frequency and the maximum gain of this antenna is 8.06 dB at 21.50 GHz, which is much better than as obtained in earlier studies [6], [10], [12], [13]. The antenna gain looks rather good, and by placing this single element antenna in an array, the gain can be increased more which is suitable for longer range, better signal quality and efficient energy radiation in a particular direction.…”
Section: Resultsmentioning
confidence: 52%
“…Therefore, the yz patterns can be considered as the vertical plane radiation patterns. The proposed UWB antennas in this study have been compared with similar works that have been reported in the literature [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. From the provided results that are illustrated in Tab.…”
Section: Simulation Resultsmentioning
confidence: 98%
“…Let be the velocity of propagation electromagnetic wave into the human breast tissue as given in Equation (8). ) (9) where, f etr = f tr =…”
Section: Evaluation Of Depth Of Tumor In Human Breast Model For Vario...mentioning
confidence: 99%
“…The antenna gain is minimum because of lower surface area. A compact high gain antenna operates at UWB band results in high gain and has omnidirectional radiation [9]. A coplanar waveguide fed with conductor backed antenna operates at wide bandwidth and results in average gain of 5 dBi [10].…”
Section: Introductionmentioning
confidence: 99%